2016
DOI: 10.1111/jcms.12359
|View full text |Cite
|
Sign up to set email alerts
|

Loose Ties or Strong Bonds? The Effect of a Commissioner's Nationality and Partisanship on Voting in the Council

Abstract: This article studies the consequences of the increased appointment of political Commissioners for the legislative process. Based on the principal–agent relation between the Council and the Commission, it is hypothesized that governments sharing national and partisan ties with the Commissioner responsible for a legislative proposal are less likely to cast a negative vote. Analysing 687 contested legislative proposals voted upon between 1999 and 2014, it is found that a Member State is indeed less likely to vote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…This is consistent with existing research on the homogeneity of green parties at a European level, which makes it easier and obvious to establish a strong social identification (Ennser, 2010). The observation that national identities are still more important than party identities to individual voting in the EP speaks to the results of existing research (Killermann, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with existing research on the homogeneity of green parties at a European level, which makes it easier and obvious to establish a strong social identification (Ennser, 2010). The observation that national identities are still more important than party identities to individual voting in the EP speaks to the results of existing research (Killermann, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…However, party cohesion is still lower than in most national parliaments (Faas, 2003), which is often traced back to national factors like the occasional conflict of political group lines with national party lines or overarching national interests. It is still contested and dependent on study designs and subjects whether ideology is found to be the main predictor of voting or whether national factors are revealed as the most important influence on voting behaviour in the EU legislative (Killermann, 2016). In particular, when an issue is nationally salient, national governments may decide to lobby their national MEPs in order to influence voting outcomes (Costello and Thomson, 2016).…”
Section: State Of the Art: Voting And Decision‐making In The European...mentioning
confidence: 99%
See 1 more Smart Citation
“…Politicians use IO officials of the same nationality to influence IOs (Urpelainen 2012;Kleine 2013). Within the European Commission, which is supposed to approximate the ideal of a post-national bureaucracy, governments use their connections to specific Commissioners, whose nationality affects many aspects of EU's functioning, including policy initiation, voting in the Council of the EU, and budget allocations (Thomson 2008;Wonka 2008;Killermann 2016;Gehring and Schneider 2018). At the UN, member states have used nationals in strategical positions to influence the work of permanent departments and temporary missions (Salton 2017;Johns 2007).…”
Section: Io Appointments and Member States' Lobbyingmentioning
confidence: 99%
“…They are, therefore, not fully independent. A study concluded that supervisors have a tendency to vote in favour of the members of the same party in councils(Killermann, 2016).29 For instance,Giavazzi et al (2021) suggests that rules should target a medium-term target for the debt-to-GDP ratio operationalised through a single instrument: a multi-year ceiling on the primary spending net of interest payments, automatic stabilisers, and spending-for-the future items. The debt target could be reviewed depending on cyclical indicators and the monetary policy from the European Central Bank while the expenditure ceiling can be reviewed every periodically or when tax revenues reform is made so that expenditures can grow without damaging the prospects for the primary balance.…”
mentioning
confidence: 99%